Bibliotecas Escolares de Rio Verde-GO: uma possível política municipal de leitura - Lopes, Leonardo Montes [UNESP] (2014)
This thesis offers an analysis of the public policy of investment and practices of reading in the Public Municipal Libraries in the city of Rio Verde - GO. Three different libraries were chosen in the mentioned city; at the same time, it was done a research about a rewarding experience named Viva Leitura; and for that, we had as yardstick three public libraries from the municipal segment of Londrina -PR. For the preparation of this work, a lot of reading was done and also a historical rescue of the trajectory of public library in Brazil and abroad. The research is qualitative and quantitative and was based on bibliographic works from authors as: Bakhtin, Cosson, Foucault, Freire, Kuhlthau, Chartier, Girotto e Souza, Silva, and more. Analysis of documents and interviews with six people who work at public libraries were done. Three of these people are from the city of Rio Verde and the other three from Londrina.Three school principals of Rio Verde were also interviewed, and so did the Education Secretaries from Rio Verde and Londrina. A study about the running conditions, the investment policy in physical structure; reading projects done at school libraries in Rio Verde and the library-community relationship was also done. Through this work we concluded that the school libraries in Rio Verde need investments in structural areas and in the qualification of teachers who work at these libraries. We also concluded what a great importance it is the involvement of community and public power in an effort to extend these places and make them stronger...